Impact of Diversified Chemical and Biostimulator Protection on Yield, Health Status, Mycotoxin Level, and Economic Profitability in Spring Wheat (Triticum aestivum L.) Cultivation - Bozena Lozowicka; Piotr Iwaniuk; Rafal Konecki; Piotr Kaczynski; Nurlan Kuldybayev; Yerlan Dutbayev (Agronomy, 2022)
Biostimulators with chemical protection are a challenge in sustainable agriculture to obtain high yield, healthy, and pesticide-free wheat. The aim of this four-year spring wheat field experiment was to assess the effectivity of using herbicide, mixed fungicides protection, and a humic biostimulator. The following treatments were tested: biostimulator (S), sulfosulfuron (H), H + S, H + propiconazole + cyproconazole/spiroxamin + tebuconazole + triadimenol (H + F1 + F2), and H + F1 + F2 + S. Evaluations of wheat yield and fungal diseases (Septoria tritici blotch, eyespot, sharp eyespot, Fusarium spp.) were performed using visual and qPCR methods. Thirteen mycotoxins were analyzed by LC–MS/MS. Infestations of six weeds were examined visually. Temperatures and precipitation data of the vegetative seasons were monitored. Precipitation most affected the occurrence of leaf diseases despite the same chemical/biostimulator treatments (up to 48% Septoria tritici blotch severity for the S treatment). The highest mean yield was obtained for H + F1 + F2 + S (5.27 t ha−1), while the lowest level of mycotoxins was obtained for H + F1 + F2 (221.68 µg kg−1). For H + S, a greater reduction of mycotoxins was determined compared to the H treatment (27.18%), as well as a higher severity of eyespot (18%) and sharp eyespot (24%). In 2017–2020, the most effective reduction of weed infestation and Fusarium spp. DNA on ears was indicated for H + F1 + F2 (16 g and 0.88 pg g−1 DNA, respectively). The greatest saved production value (196.15€) was determined for H + F1 + F2 + S.